Intervensi Psikologis Berbasis Permainan dalam Konseling Kelompok untuk Meningkatkan Motivasi Belajar - Eka Safira Agustina; Asri Rejeki (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
The increase in academic load and the demands of graduation standards faced by students from elementary to junior high school place unique pressures on each student. Enhancing learning motivation can serve as a strength to help them face these challenges. This study aims to increase students' learning motivation through a game-based psychological intervention in group counseling. An experimental approach with a one-group pretest-posttest design was chosen for this study. The population and sample consisted of all 27 sixth-grade students at SD X. Data were collected and described using a learning motivation questionnaire, then analyzed with nonparametric statistics using a paired T-test. The results showed p = 0.000 < 0.05, indicating a significant difference between pretest and posttest scores after the intervention. It can be concluded that game-based psychological interventions in group counseling effectively increase students' learning motivation. This intervention can be utilized by teachers or counselors at school to support students' learning motivation.